2014
DOI: 10.7314/apjcp.2014.15.12.4969
|View full text |Cite
|
Sign up to set email alerts
|

Effects of miR-152 on Cell Growth Inhibition, Motility Suppression and Apoptosis Induction in Hepatocellular Carcinoma Cells

Abstract: Background: miR-152 is involved in the genesis and development of several malignancies. However, its role in HCC has not been fully clarified. The aim of this study was to investigate the clinicopathological significance of miR-152 and its effect on the malignant phenotype of HCC cells. Methods: miR-152 expression was detected using real-time quantitative RT-PCR in 89 pairs of HCC formalin-fixed paraffin-embedded and their adjacent tissues. Functionally, in vitro effects and mechanisms of action of miR-152 on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 41 publications
(73 reference statements)
0
43
0
Order By: Relevance
“…Many studies have revealed miRNAs could influence colorectal tumor growth, migration, invasion, angiogenesis, metastasis, diagnosis and prognosis (Dang et al, 2014;Yin et al, 2014;Zhao et al, 2014). Li et al showed that miR-451 is downregulated in colorectal carcinoma and has a repressive role in CRC cells by inhibiting cell growth through down-regulating the P13K/AKT pathway .…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have revealed miRNAs could influence colorectal tumor growth, migration, invasion, angiogenesis, metastasis, diagnosis and prognosis (Dang et al, 2014;Yin et al, 2014;Zhao et al, 2014). Li et al showed that miR-451 is downregulated in colorectal carcinoma and has a repressive role in CRC cells by inhibiting cell growth through down-regulating the P13K/AKT pathway .…”
Section: Discussionmentioning
confidence: 99%
“…Real-time qPCR was performed with Applied Biosystems PCR7900. The NEAT1 expression was calculated with the formula 2 -Δcq (Chen et al, 2013c;Dang et al, 2014;Rong et al, 2014).…”
Section: Rt-qpcrmentioning
confidence: 99%
“…Ki-67 has been used to distinguish growing cells from non-growing cells (Haroon et al, 2013;Dang et al, 2014;Huang and Chen, 2014). Furthermore, Ki-67 is a reliable indicator of tumor cell proliferative activity that has been associated with the histological grade for glioma (Hu et al, 2013).…”
Section: Introductionmentioning
confidence: 99%